Soy Flour-Based Snack Bar as Potential Snack Alternative for Diabetes Mellitus - Naufal Muharam Nurdin; Hana Fitria Navratilova; Karina Rahmadia Ekawidyani; Dessy Pratiwi; Mohamad Yulianto Kurniawan (Jurnal Gizi dan Pangan, 2020)
This study aimed to determine the Glycaemic Index (GI), Glycaemic Response (GR) and Glycaemic Load (GL) of soy flour-based snack bars in healthy volunteers. An open label randomized controlled trial with crossover study design was done involving eighty adults aged 18‒50 years. The glycaemic index was calculated using Incremental Area Under the Blood Glucose Response Curve (iAUC). Friedman’s test was used to determine difference of glucose iAUC between WF and SF. Wilcoxon test was used to determine difference of blood glucose peak, time to blood glucose peak, GI and GR between snack bars. The result observed that median (Q1‒Q3) of GI were 88.4 (42.3‒115.8); WF: 36.6 (21.8‒47.9) (Product SF3, Banana); 36.3 (18.9‒49.2) (Product SF6, Crispy White Chocolate Macadamia); 29.9 (22.0‒43.3) (Product SF5, Crispy Vanilla); 25.9 (17.8‒35.4) (Product SF4; Strawberry); 20.2 (15.3‒22.2) (Product SF1, Almond Chocolate); and 7.1 (5.4‒17.0) (Product SF2, Raisin Almond). We found that GL of WF was (17.7). While, the GL of snack bars made from SF were 4.9 (Product SF3, Banana), 4.1 (Product SF4, Strawberry), 1.9 (Product SF1, Almond Chocolate); 1.8 (Product SF6, Crispy White Chocolate Macadamia), 1.6 (Product SF5, Crispy Vanilla), and 0.9 (Product SF2, Raisin Almond). Friedman statistical test showed significant differences on the blood glucose iAUC between SF and WF (p<0.001). SF snack bar showed different GR results, where the area of each products (SF1‒SF6) curve was significantly lower than WF. Based on Wilcoxon test, the GI and GR of SF were significantly lower than WF (p<0.05). In conclusion, SF snack bars can be classified as a low GI-source snack bar with a low category of glycaemic load; and had relatively high fibre, protein, and fat content which contributed to a lower GI value. Thus, it is a potential snacks alternative for people with blood glucose concerns.